Association between adjuvant docetaxel-based chemotherapy and breast cancer-related lymphedema. Issue 3 (March 2017) - Zhu, Wen; Li, Dan; Li, Xiaoqin; Ren, Jin; Chen, Wenqi; Gu, Hangang; Shu, Yongqian; Wang, Deqiang
Abstract : Docetaxel-based chemotherapy can lead to fluid retention and secondary peripheral edema of the extremities, but its association with lymphedema remains unclear. In this study, we retrospectively investigated the relationship between adjuvant docetaxel-based chemotherapy and breast cancer-related lymphedema. Patients with stage II/III breast cancer who received adjuvant chemotherapy were evaluated for lymphedema on the basis of arm circumference measurements. The incidence and risk factors of lymphedema were determined by Kaplan–Meier and Cox proportional hazard analyses. A total of 320 patients were included. Specifically, 182 patients received docetaxel and 138 patients did not receive docetaxel. Compared with docetaxel-free chemotherapy, docetaxel-based chemotherapy significantly increased the 2.5-year cumulative incidence of all-grade lymphedema (19.91 vs. 32.09%; P =0.011), which was further verified in grade 1–2 ( P =0.012), but not in grade 3 lymphedema ( P =0.448). Similar results were found in a comparison between docetaxel and nontaxane, but not in a comparison between docetaxel and other taxanes. Multivariate analysis showed that docetaxel-based chemotherapy is an independent risk factor for both all-grade (hazard ratio=1.73; P =0.017) and grade 1–2 lymphedema (hazard ratio=1.87; P =0.022). In conclusion, adjuvant docetaxel-based chemotherapy significantly increased the risk of breast cancer-related lymphedema. Abstract : Supplemental Digital Content is available in the text.